The pivotal role of oxyallyl diradicals in photo-Favorskii rearrangements: transient spectroscopic and computational studies - Šolomek, Tomáš; Heger, Dominik; Ngoy, Bokolombe P; Givens, Richard S; Klán, Petr (Journal of the American Chemical Society, 2013)
The photochemistry of the hydroxybenzocycloalkanonyl derivatives 6b-e provides the triplet oxyallyl diradicals (3)9 that decay via intersystem crossing to their more stable singlet isomers (1)9. Vibrationally resolved transient spectra of (3)9 were recorded by pump-probe spectroscopy and laser flash photolysis. It was found that the ring strain dependent rate of intersystem crossing is the rate-limiting step in the formation of photo-Favorskii or solvolysis reaction products in water. The reactivities of open-shell singlet oxyallyls (1)9a-e determine the product ratios due to their relative abilities to form the corresponding cyclopropanones 10. The smallest five-membered derivative, (1)9b, represents the first example of an oxyallyl diradicaloid that cannot form cyclopropanone 10b or the isomeric allene oxide 13b; instead, it is eventually trapped by water to form the sole solvolysis product 12b. Our observations provide a comprehensive overview of the role of oxyallyl diradicals in reaction mechanisms and offer a new strategy to stabilize open-shell singlet diradicals.